Effect of the parameters of a gas-discharge plasma on the equilibrium temperature and floating potential of macroparticle - Bizyukov, A.A.; Chibisov, A.D.; Romashchenko, E.V. (Вопросы атомной науки и техники, 2012)
The effect of discharge plasma density and energy of the electron beam on the potential of the solitary macroparticle (MP) has been investigated. It is shown that increasing of the plasma density as well as the electron beam energy lead to heating of the MP and to the appearance of the effect of thermionic emission, which leads to a decrease in the absolute value of its potential. The mutual influence on each other of the MP charging processes and its heating has been studied. Исследовано влияние плотности газоразрядной плазмы и энергии электронного пучка на потенциал уединенной макрочастциы (МЧ). Показано, что увеличение плотности плазмы, а также энергии электронного пучка приводят к интенсивному разогреву МЧ и возникновению эффекта термоэлектронной эмиссии, который приводит к снижению по абсолютной величине ее потенциала. Изучено взаимное влияние процессов зарядки МЧ и ее разогрева. Досліджено вплив густини газорозрядної плазми і енергії електронного пучка на потенціал відокремленої макрочастки (МЧ). Показано, що збільшення густини плазми, а також енергії електронного пучка призводять до інтенсивного розігріву МЧ і виникнення ефекту термоелектронної емісії, що призводить до зниження за абсолютною величиною її потенціалу. Вивчено взаємний вплив процесів зарядки МЧ і її розігріву.